Fatal Outcome in Hemiconvulsion-Hemiplegia Syndrome. (March 2014) - Jayakody, Himali; Joshi, Charuta
Hemiplegia-hemiconvulsion-epilepsy syndrome is characterized by prolonged unilateral clonic seizures in a child followed by the development of hemiplegia. Focal status epilepticus results in unilateral cerebral edema of the epileptic hemisphere in the acute phase followed by cerebral hemiatrophy. Literature in the last 5 years does not describe malignant cerebral edema or resultant death. We report a case of a 3-year-old girl with hemiplegia-hemiconvulsion-epilepsy syndrome who died due to malignant cerebral edema and temporal lobe herniation. The first indication of worsening of clinical status after being seizure free was voltage suppression on continuous electroencephalography (EEG). We describe neuroimaging, EEG findings, and neuropathologic findings at autopsy and review pertinent literature. We also evaluate the evolving role of continuous EEG monitoring in the pediatric intensive care unit.